PENGARUH SENAM YOGA TERHADAP KREATIVITAS PADA DUA KELOMPOK MAHASISWA FAKULTAS PSIKOLOGI UNIVERSITAS PERSADA INDONESIA Y.A.I. - Agnes Irawati Kother (Psibernetika, 2011)
Creativity allows the emergence of new discoveries in science and technology. One effective way to increase creativity is a yoga exercise that will facilitate the function of the right hemisphere of the brain that is part of the brain that thinks creatively. Issues to be investigated in this study is: "Are there any yoga exercise influence on creativity?" This study aims to determine the effect of yoga exercise their creativity. The formulation of the hypothesis of this study were: Subjects who received treatment by following the yoga exercises will get an increase in score of CQ (Creativity Quotient) is significantly higher than subjects who did not follow the yoga exercises. Creativity (Variable Experiment) is a process that is reflected in the fluency, flexibility, originality and elaboration in thinking, a verbal creativity test scores of Utami Munandar. Gymnastics Yoga (Treatment) is a system of exercises practiced as part of the discipline to control your body and mind, consists of three components: stretching, breathing and meditation. Population and sample of this study were two groups of students of the Faculty of Psychology University of Indonesia YAI Persada, which is 30 students for the control group (KK) and 30 students for the experimental group (KE). To measure creativity in this study used the Verbal Creativity Test developed by Utami Munandar. The study design used is the design of the two groups (inter-group) with type nonrandomized Control Group Pretest-posttest design. Statistical analysis techniques used were "independent sample t-test" and the data processing performed by using SPSS "for Windows" version 15.0. In this study, we conducted control of the IQ (Intelligence Quotience). Test of Hypothesis (t test) against the gain of both groups obtained scores: T = 8.048, p = 0.000, p <0.05 then H0, which reads: Subjects who received treatment by following the yoga exercises will get an increase in score of CQ (Creativity Quotient), which did not differ significantly with subjects that do not follow gymnastics yoga, rejected. Keyword: yoga exercises, creativity, students